Dynamic simulations of Vatnajökull ice cap from 1980 to 2300. Issue 255 (10th February 2020) - Schmidt, Louise Steffensen; Ađalgeirsdóttir, Guðfinna; Pálsson, Finnur; Langen, Peter L.; Guđmundsson, Sverrir; Björnsson, Helgi
Abstract: Like most ice caps and glaciers worldwide, Icelandic glaciers are retreating in a warming climate. Here, the evolution of Vatnajökull ice cap, Iceland, from 1980 to 2300 is simulated by forcing the Parallel Ice Sheet Model (PISM) with output from Regional Climate Models (RCMs). For climate simulations of the recent past, HARMONIE-AROME reanalysis-forced simulations are used, while for future climate conditions, high-resolution (5.5 km) simulations from the RCM HIRHAM5 are used in addition to available CORDEX simulations (12 km). The glacier evolution is modelled using the RCP 4.5 and RCP 8.5 scenarios until 2100. To extend the time series, the 2081–2100 climate forcing is repeated until 2300. For RCP 4.5, the ice cap loses 31–64% of its volume and 13–37% of its area by 2300 depending on the used model forcing. For RCP 8.5, the volume decrease is 51–94% and the area decrease is 24–80% by 2300. In addition, the effect of elevation feedbacks is investigated by adding a precipitation and temperature lapse rate to the HIRHAM5 simulations. By 2300, the lapse rate runs have a 9–14% smaller volume and a 9–20% smaller area than the runs without a lapse rate correction.